High-resolution STEM investigation of the role of dislocations during decomposition of Ti1-xAlxNy. (May 2023) - Salamania, J.; Kwick, K.M. Calamba; Sangiovanni, D.G.; Tasnádi, F.; Abrikosov, I.A.; Rogström, L.; Johnson, L.J.S.; Odén, M.
Abstract: The defect structures forming during high-temperature decomposition of Ti1-x Alx Ny films were investigated through high-resolution scanning transmission electron microscopy. After annealing to 950 °C, misfit edge dislocations and a / 6 〈 112 〉 { 111 } partial dislocations permeate the interface between TiN-rich and AlN-rich domains to accommodate lattice misfits during spinodal decomposition. The stacking fault energy associated with the partial dislocations decreases with increasing Al content, which facilitates the coherent cubic to wurtzite structure transition of AlN-rich domains. The wurtzite AlN-rich structure is recovered when every third cubic {111} plane is shifted by a / 6 along the [211] direction. After annealing to 1100 °C, a temperature where coarsening dominates the microstructure evolution, we observe intersections of stacking faults, which form sessile locks at the interface of the TiN- and AlN-rich domains. These observed defect structures facilitate the formation of semicoherent interfaces and contribute to hardening in Ti1-x Alx Ny . Graphical abstract: Image, graphical abstract